2012
DOI: 10.1166/jnn.2012.5752
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Phosphrous Doping in ZnTe Nanowires with Enhanced p-type Conductivity

Abstract: Single-crystalline undoped and phosphrous-doped (P-doped) p-type ZnTe nanowires (NWs) were synthesized via a simple vapor transport and deposition method. Both undoped and P-doped ZnTe nanowires have zinc blende structure and uniform geometry. X-ray diffraction peaks of the P-doped ZnTe nanowires show an obvious shift toward higher diffraction angle as compared with the undoped ZnTe nanowires. X-ray photoelectron spectroscopy confirms the existence of P-dopant in the ZnTe nanowires. Field-effect transistors ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…When paired with a reactive interface, transfer printing can enable the delivery of monomolecular layers with regional p-/n-doping properties onto a semiconductor interface necessary for the development of ultrashallow doping strategies. Specifically, the immobilization of inorganic atoms, such as phosphorus and boron, to silicon is an essential component in the fabrication of ultrashallow doping interfaces for next-generation complementary metal–oxide–semiconductor (CMOS) transistors. , To maintain low series resistance in sub-10 nm CMOS transistors, surface junctions should exhibit abrupt depth profiles and high phosphorus/boron concentrations that help to negate short-channel effects. Such properties cannot be achieved with current ion beam implantation techniques, which either produce broad, low-concentration dopant zones or inflict crystallographic damage upon the surface of a substrate over a micrometer range. Alternatively, plasma doping studies have demonstrated the ability to generate more conformal doping profiles; however, surface quality concerns arising from the entrapment of dopant molecules at the oxide interface during implantation have also been reported . Scanning tunneling microscopy (STM) has been shown to produce atomically precise phosphorus-doped regions on silicon using a STM probe to cleave Si–H bonds and generate strong and chemically inert Si–P bonds in a site-by-site manner. , However, this deposition and patterning technique has very low throughput and requires ultrahigh vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When paired with a reactive interface, transfer printing can enable the delivery of monomolecular layers with regional p-/n-doping properties onto a semiconductor interface necessary for the development of ultrashallow doping strategies. Specifically, the immobilization of inorganic atoms, such as phosphorus and boron, to silicon is an essential component in the fabrication of ultrashallow doping interfaces for next-generation complementary metal–oxide–semiconductor (CMOS) transistors. , To maintain low series resistance in sub-10 nm CMOS transistors, surface junctions should exhibit abrupt depth profiles and high phosphorus/boron concentrations that help to negate short-channel effects. Such properties cannot be achieved with current ion beam implantation techniques, which either produce broad, low-concentration dopant zones or inflict crystallographic damage upon the surface of a substrate over a micrometer range. Alternatively, plasma doping studies have demonstrated the ability to generate more conformal doping profiles; however, surface quality concerns arising from the entrapment of dopant molecules at the oxide interface during implantation have also been reported . Scanning tunneling microscopy (STM) has been shown to produce atomically precise phosphorus-doped regions on silicon using a STM probe to cleave Si–H bonds and generate strong and chemically inert Si–P bonds in a site-by-site manner. , However, this deposition and patterning technique has very low throughput and requires ultrahigh vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the immobilization of inorganic atoms, such as phosphorus and boron, to silicon is an essential component in the fabrication of ultrashallow doping interfaces for next-generation complementary metal–oxide–semiconductor (CMOS) transistors. 27 , 28 To maintain low series resistance in sub-10 nm CMOS transistors, surface junctions should exhibit abrupt depth profiles and high phosphorus/boron concentrations that help to negate short-channel effects. 29 31 Such properties cannot be achieved with current ion beam implantation techniques, which either produce broad, low-concentration dopant zones or inflict crystallographic damage upon the surface of a substrate over a micrometer range.…”
Section: Introductionmentioning
confidence: 99%